Unfinished business: an appraisal of the latest UNDS reform resolution - Max-Otto Baumann; Silke Weinlich (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
Can the United Nations Development System (UNDS) become a resourceful, well-organised partner for member states in implementing the 2030 Agenda? The UNDS is the biggest multilateral development actor, accounting for 18.4 billion, or 33 per cent, of multilateral aid in 2015. Its functions range from providing a forum for dialogue, decision-making and norm-setting, to research, advocacy, technical assistance and humanitarian aid. Numerous governments, including those of high-income countries, are counting on the UN's assistance for advancing their development in a sustainable way. More than any other development organisation, the UNDS needs to adjust in order to fulfil these expectations. In May 2018, UN member states set the course for reforming the UNDS by agreeing on a draft resolution. The resolution contains five potentially transformative decisions that will bring the UNDS a step closer to being “fit for purpose”, the term under which the reform process was initiated more than three years ago. The global structures of the UNDS are to be strengthened, making the system more strategic and accountable; Resident Coordinators are to coordinate more effectively and objectively; their funding will be guaranteed by a new 1 per cent levy on tightly earmarked contributions; common business operations are to be advanced, with potential efficiency gains of 380 million per year; and the UN's vast network of country offices is to be consolidated for more efficiency and effectiveness. In the context of a resurgence of nationalist agendas and mistrust of multilateral approaches in many corners of the world, agreement on the draft resolution is a significant achievement. However, the resolution falls short of the reform proposals suggested by the Secretary-General and others. Member states chose, yet again, an incremental approach. Key novelties of the 2030 Agenda, such as universality and policy integration, have not been translated into meaningful organisational adjustments. There is still a long way to go if the UNDS is to become the UN's universal branch, facilitating the implementation of the 17 Sustainable Development Goals (SDGs) in and by all countries of the world. Nevertheless, the resolution is a viable starting point. Member states must play their part in making the reform a success. They need to push for reform in the respective governing boards across the system – this should be the most obvious and effective way of advancing the reform. They could ask the heads of all UNDS entities to subscribe to the reforms and to initiate all necessary adjustments. Furthermore, they should ensure coherence within their own governments and speak with one voice – for the implementation of the reforms, as well as for the acceleration of the implementation of Agenda 2030. A more reliable funding for the UNDS as a whole, and specifically for the strengthened country coordination, will also be decisive for the changes to be effective. Member states across all income groups should show their support for the reforms and engage in the Funding Compact. They should be prepared to bolster multilateralism in uncertain times by stepping up core contributions and reducing tight earmarking. Specifically, they could link an increase in core-funding to advances in the area of common business operations, which would improve efficiency and enable smoother collaboration among UN agencies.
Keywords: 330; Agenda 2030; Deutsche + Europäische + multilaterale Entwicklungspolitik